Colchicine for prevention of post-operative atrial fibrillation: Meta-analysis of randomized controlled trials - Ge, Peibing; Fu, Yu; Su, Qi; Jin, Mengdi; Guo, Li; Miao, Congliang; Zhu, Shun; Zhuang, Jinqiang; Zhang, Zhi; Hong, Jiang (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study intended to assess the efficacy of colchicine for prevention of post-operative atrial fibrillation (AF). Background: Post-operative AF is a common complication of surgery operations. Inflammation plays a crucial role in the pathogenesis of Post-operative AF. Colchicine, a potent anti-inflammatory drug, may have a role in mitigating the incidence of post-operative AF. Methods: We searched Cochrane Library, Web of Science, PubMed, China National Knowledge Infrastructure (CNKI), Database of Chinese sci-tech periodicals (COVIP), and Wanfang Database for randomized controlled trials (RCTs) comparing colchicine versus placebo, or usual care for prevention of post-operative AF. The main outcome was the occurrence of AF post operation, which includes cardiac surgery, lung surgery, or pulmonary vein isolation. The estimated risk ratio (RR) for the occurrence of post-operative AF was evaluated using a random-effects model. The safety end point was the development of any side effects. Results: A total of 12 RCTs with 2274 patients were eventually included in this meta-analysis, where 1141 patients received colchicine and 1133 patients received placebo or usual care. Perioperative colchicine treatment was related to a decreased incidence of post-operative AF (RR: 0.65; 95% confidence interval [CI]: 0.56 to 0.75, p＜0.001). Although the incidence of gastrointestinal side effects was increased with colchicine therapy when compared to placebo (RR=2.49, 95% CI 1.85 to 3.34, p<0.001), the incidence of major adverse events was not increased (RR=0.86, 95% CI 0.46 to 1.60, p=0.64). Conclusions: In conclusion, the results of our meta-analysis suggest that colchicine treatment could lower the incidence of post-operative AF. Further studies are needed to determine the optimal colchicine treatment regime to minimize the incidence of adverse events.